Lymphoma-associated hemophagocytic syndrome: a retrospective study from a single center - Na Li; Ming Jiang; Wan-chun Wu; Hui-jie Zhou; Li-qun Zou (Hematology, 2022)
Lymphoma-associated hemophagocytic syndrome (LAHS) is a rare and life-threatening clinical syndrome with rapidly deteriorating health and high mortality. We retrospectively analyzed clinical features and prognostic factors from 117 patients diagnosed with LAHS. The cumulative incidence rate of LAHS was 4.0% (117/2906). Patients were classified into B-cell LAHS (B-LAHS, n = 22) and T/natural killer (NK)-cell LAHS (T/NK-LAHS, n = 95) groups. Patients with T/NK-LAHS were younger and had lower neutrophil counts and fibrinogen values, higher LDH and transaminase levels, and were more likely to develop hemophagocytic syndrome (HPS) during the clinical course than those with B-LAHS. The median survival time for the entire cohort was 57 days, and for the T/NK-LAHS and B-LAHS groups, it was 52 and 154 days, respectively, after the diagnosis of LAHS. Patients with B-LAHS had superior 1-year OS (p = 0.003, 36.4% versus 14.5%) compared with those with T/NK-LAHS. Prognostic factor analysis revealed that elevated LDH levels (LDH > 1000 IU/L) (p = 0.004), T/NK-cell lineage (p < 0.001) and HPS onset at relapse (p = 0.001) were strongly associated with early death. For patients diagnosed with T/NK-LAHS, in addition to LDH levels and HPS onset status, high EBV-DNA copies (≥4,450 copies/mL) (p = 0.016) were also related to poor prognosis of T/NK-LAHS.